THE IMPACT OF EXTRACURRICULAR ACTIVITIES ON ACADEMIC PERFORMANCE IN KAZAKHSTANI RESEARCH-ORIENTED UNIVERSITIES: A MIXED-METHODS STUDY - Toleubay, Altynbek (Nazarbayev University Graduate School of Education, 2025)
Extracurricular activities (ECAs) are essential in helping students grow holistically. However, their influence within the context of research-oriented universities in Kazakhstan remains understudied. This mixed-methods study aimed to identify the types of ECAs students participate in, explore the relationship between ECA engagement and academic performance, and evaluate the role of institutional support in facilitating meaningful student involvement. The study involved 389 students from four research-oriented universities in Kazakhstan. Quantitative data were collected through an online survey, and qualitative data were received from semi-structured interviews with 10 participants selected via purposive sampling. Findings revealed that students engaged in various ECAs, including academic clubs, volunteering, sports, and student governance. Although no statistically significant correlation was found between ECA participation and GPA (ρ = -0.070, p = 0.170), qualitative insights indicated that overcommitment could interfere with academic focus, aligning with the Zero-Sum Framework (Marsh & Kleitman, 2002). Conversely, institutional support was a significant factor in improving the benefits of ECA involvement, which is consistent with the Developmental Framework (Fredricks & Eccles, 2006). Students also cited internal motivations such as skill development and autonomy, reinforcing the relevance of the Self-Determination Theory (Deci & Ryan, 2000). Overall, the findings highlight the need for more strategic engagement policies and cross-institutional collaboration to improve the accessibility and quality of extracurricular opportunities for students across diverse academic and socioeconomic backgrounds.
Keywords: academic performance; institutional support; student engagement; personal development; research-oriented universities; Kazakhstan; mixed-methods research.; extracurricular activities; holistic development; student clubs; Kazakhstani universities; Research oriented universities; Type of access: Open